2009
DOI: 10.1128/cvi.00310-08
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity of Paracoccidioides brasiliensis , Histoplasma capsulatum , and Cryptococcus Species in the Commercial Platelia Aspergillus Enzyme Immunoassay

Abstract: Cross-reactivity in the Platelia Aspergillus enzyme immunoassay was evaluated using 120 sera from patients with paracoccidioidomycosis, histoplasmosis, and cryptococcosis. At a cutoff value of 0.5, positivity rates were 50%, 67%, and 50%, respectively. The implications for these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 9 publications
0
44
0
Order By: Relevance
“…Since GM is released during fungal hyphal growth, its detection in circulation or in other body fluids allows for an early diagnosis of invasive aspergillosis (IA) 4 . However, when interpreting a positive GM result in a patient with suspected IA, one might consider the variety of factors that can potentially interfere with the test, including antibiotic use, dietary factors and cross-reactivity with non-Aspergillus fungi 3,9,10 . Although early investigations have suggested that GM levels may vary among Aspergillus species 7 , there is still only very limited data to support this.…”
Section: Introductionmentioning
confidence: 99%
“…Since GM is released during fungal hyphal growth, its detection in circulation or in other body fluids allows for an early diagnosis of invasive aspergillosis (IA) 4 . However, when interpreting a positive GM result in a patient with suspected IA, one might consider the variety of factors that can potentially interfere with the test, including antibiotic use, dietary factors and cross-reactivity with non-Aspergillus fungi 3,9,10 . Although early investigations have suggested that GM levels may vary among Aspergillus species 7 , there is still only very limited data to support this.…”
Section: Introductionmentioning
confidence: 99%
“…The epitope detected by the EB-A2 monoclonal antibody employed in the EIA is not exclusively present in Aspergillus species. This epitope is contained also in antigens of other molds, including Penicillium, Paecilomyces, Trichothecium, Geotrichum, and Myceliophthora, of dimorphic fungi, such as Blastomyces dermatitidis and Histoplasma capsulatum, and also of yeasts (1,3,4,8,20,21). Cross-reactivity of Fusarium spp.…”
mentioning
confidence: 99%
“…Cross-reactivity with antigens released by a large number of fungi has been reported in the literature (1,3,4,8,20,21). Test specificity with exoantigens of Fusarium cultures is controversial (1,6,16).…”
mentioning
confidence: 99%
“…Ângela Leitzke Cabana [1] , Josiara Furtado Mendes [1] , Gabriel Baracy Klafke [2] , Tchana Martinez Brandolt [3] , Aryse Martins Melo [4], [5] , Mário Carlos Araújo Meireles [1] and Melissa Orzechowski Xavier [2], [4] [1]. Galactomannan (GM) is a hydrosoluble polysaccharide derived from the fungal cell wall.…”
Section: Short Communicationmentioning
confidence: 99%